A Simple Thermal Dynamics Model and Parameter Identification of District Heating Network. (2017) - Wang, Na; You, Shijun; Zheng, Wandong; Zhang, Huan; Zheng, Xuejing; Ye, Tianzhen
Abstract: The existence of time delay usually results in the mismatch between the heat source output and the users' heating load. In the research, a dynamic model is built to predict the supply water temperature in the substation and the heat loss from the heat source to the substation by identifying the time delay, α and β. α and β are parameters obtained by Regression. α is determined by the length of pipeline, velocity, heat transfer coefficient, etc., β is determined by outdoor air temperature besides those above elements. In the feasibility and prediction ability analysis of the model, two groups of tested supply water temperature in the substation are fitted well with the predicted supply water temperatures, respectively. Results show that the proposed method can improve the prediction accuracy of the supply water temperature in the heating substation, and the prediction error of the supply line heat loss can be restricted within -10%-2%. This indicates that the model have great ability in the temperature prediction and heat loss calculation.